KINERJA KEUANGAN TERHADAP EFFECTIVE TAX RATE SEKTOR INFRASTRUKTUR, UTILITAS, DAN TRANSPORTASI DI INDONESIA: indonesia - Gunawan, Hadi; Evi Marlina, Maria Assumpta; Ismawati, Anastasia Filiana (Media Akuntansi dan Perpajakan Indonesia, 2020)
This research has been conducted to analyze the effect of financial performance on the effective tax rate. The effective tax rate is the determinant of the company’s income tax percentage payment. This research chooses infrastructure, utility and transportation sectors companies, considering the mission of the government era of Jokowi namely equitable development. In addition, the Business Entity Development Cooperation (KPBU) has been conducted to accelerate the realization of this equitable development. The role of the private sector is also used in equitable development. The writer is interested in observing whether the taxes paid have been effective or not. The independent variables in this study are profitability, intensity fixed assets, leverage and firm size, the dependent variable of this study is the effective tax rate. The sample of this research is companies in the infrastructure, utility and transportation sectors which are listed on the Indonesia Stock Exchange (IDX) with the research period 2014–2018. Data collection uses purposive sampling method. The population used in this study is 52 companies. Based on the results of observation, the sample that can be used in this study is 42 companies. This study uses data analysis multiple linear regression. The results of this study indicate that profitability has a negative effect, the intensity of fixed assets a negative effect, leverage has a positive effect, and company size has a negative significant effect on effective tax rate.